Regional, age and sex differences in baseline characteristics of patients enrolled in the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS). Issue 4 (13th February 2015) - Bethel, M. A.; Green, J. B.; Milton, J.; Tajar, A.; Engel, S. S.; Califf, R. M.; Holman, R. R.; on behalf of the TECOS Executive Committee
<x xml:space="preserve">Abstract</x> Aims To report baseline characteristics and cardiovascular (CV) risk management by region, age, sex and CV event type for 14 724 participants in the Trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS), a randomized, double‐blind, placebo‐controlled trial exploring whether sitagliptin added to usual type 2 diabetes (T2DM) care affects time to first event in the composite endpoint of CV death, non‐fatal myocardial infarction (MI), non‐fatal stroke or unstable angina hospitalization. Methods TECOS enrolled patients aged ≥50 years, with T2DM and CV disease from 38 countries in five regions: North America, Eastern Europe, Western Europe, Asia Pacific and Latin America. Participants had a glycated haemoglobin concentration of 6.5–8.0% (48–64 mmol/mol) and were receiving oral and/or insulin‐based antihyperglycaemic therapy. Analysis of variance or logistic regression was used to compare regional CV risk factors and treatments, referenced to North America. Results Patients had a mean [1 standard deviation (SD)] age of 66 (8) years, a median (interquartile range) diabetes duration of 9.4 (4.9, 15.3) years, and a mean (SD) body mass index 30.2 (5.7) kg/m2. Compared with North America, blood pressure and lipids were higher in all regions. Statin use was lowest in Latin America (68%) and Eastern Europe (70%) and aspirin use was lower compared with North America in all regions except Asia Pacific. Achievement of treatment targets did not differ by age group or insulin usage, but men and participants with previous MI were more likely than women or those with previous stroke or peripheral arterial disease to reach most treatment goals. Conclusion The CV risk factors of participants in TECOS are reasonably controlled, but differences in CV risk management according to region, sex and history of disease exist. This diversity will enhance the generalizability of the trial results.